The relationship between VAI, LAP, and depression and the mediation role of sleep duration–evidence from NHANES 2005–2020 - Yiqing Huang; Dan Zhao; Zhongfang Yang; Changning Wei; Xichenhui Qiu (BMC Psychiatry)
Abstract Background The relationship between obesity and mental health has attracted attention. However, large sample studies on the relationship between visceral fat obesity and depression are lacking. This study aimed to explore the relationship between visceral fat obesity and depression by using visceral adiposity index (VAI) and lipid accumulation product (LAP). Additionally, it sought to explore the potential mediating role of sleep duration in these associations. Methods The data used in the current cross-sectional investigation are from the National Health and Nutrition Examination Survey (NHANES) spanning from 2005 to 2020, including 19,659 participants. Depression was measured using the nine-item Patient Health Questionnaire. Weighted multivariable regression analysis was used to evaluate the correlation of VAI and LAP with depression. The potential non-linear relationship was determined using smooth curve fitting and threshold effect analysis. Additionally, mediation analysis was performed to investigate the potential mediating role of sleep duration. The stability of the relationship was assessed through sensitivity analysis. Results VAI and LAP were closely related to depression. In the fully adjusted model, VAI and LAP in the highest quartile increased the association of depression by 52% (OR = 1.52, 95% CI 1.20–1.92, P < 0.001) and 51% (OR = 1.51, 95% CI 1.19–1.91, P < 0.001), respectively, compared with the lowest quartile. Specific saturation effects for VAI, LAP, and depression were identified by smoothed curve fitting, with inflection points of 3.81 and 98.55, respectively. Additionally, mediation analysis revealed that 5.1% and 2.8% of the associations between VAI and LAP with depression were mediated through sleep duration. The results of the sensitivity analysis showed interactions between hypertension and cardiovascular disease in the associations of VAI, and depression (P < 0.05). Conclusion VAI and LAP are associated with depression in US adults. The associations between VAI and LAP with depression are non-linear, which may be mediated through sleep duration. The study highlights the potential of VAI and LAP as valuable tools for the prevention and management of depression.